Nonsurgical Maxillary Expansion in Adults: Report of Two Cases - Hussain, Arshad; Fatima, Shereen; Haneef, Mohammed (Journal of Orofacial Research, 2015)
Correction of maxillary transverse discrepancy requires expansion of palate by combination of orthopedic and orthodontic movements. Isolated maxillary transverse deficiency can be treated either orthodontically or surgically with assisted rapid maxillary expansion (RME). Nonsurgical expansion modalities include rapid maxillary expansion and slow maxillary expansion. Haas popularized the idea of orthodontic palatal expansion in the 1960s, and since then transverse deficiencies have been treated successfully in children and adolescents. The use of palatal expanders in adults was widely frowned upon and was generally considered to be unsuccessful. Handelman published a clinical review in 1997, proving a nonsurgical expansion in adults was possible.